Anak Indak Basuku As an Idea for Designing Information Media - Amin Wahyuda; Harissman (Jurnal Desain Komunikasi Visual, 2025)
This design proposal explores the phenomenon of Anak Indak Basuku children without a recognized clan identity within the Minangkabau matrilineal kinship system arising from interethnic marriages between Minangkabau men and non-Minangkabau women. The absence of a recognized lineage poses serious social and cultural challenges, including exclusion from traditional rights and communal identity. This project aims to raise awareness and provide solutions through the creation of a visual communication design in the form of an illustrated book and motion graphic. These media target Minangkabau youth, particularly males aged 17–23, as a strategic group likely to face such identity issues when considering marriage. The design process applies qualitative methods, including literature review, observation, interviews, and surveys, with data presented descriptively. The creative output integrates cultural values, local wisdom, and modern aesthetics to foster cultural continuity and increase public understanding of the Malakok tradition an indigenous solution that allows children to be integrated into Minangkabau clans. The result is a culturally grounded and visually engaging educational medium that contributes to the preservation of Minangkabau identity in the modern era